Gum based edible film coating for quail eggs - Vizmanos, Anthony James Hormillosa
ABSTRACT The objective of this study is to apply an edible film coating for quail eggs to retain or improve its storage quality. The first phase of the study aimed to determine which between 2.5% sodium carbonate and 100 ppm sodium hypochlorite solutions is a more suitable as a washing agent for quail eggs. Microbiological properties in terms of total plate count (TPC), yeast and mold count (YMC), and coliform count (CC) as well as the microbial load reduction (MLR) were used to evaluate the suitability of the washing agents. It was found out that the MLR of the washing agents were 76.92% (TPC) and 91.43% (CC) for the sodium hypochlorite solution and 87.23% (TPC) and 89.71% (CC) for the sodium carbonate solution. There was no observed growth for yeast and molds due to the alkaline nature of eggs, inhibiting the growth of fungi in the egg shell. Therefore, the sodium carbonate solution was selected as the more suitable washing agent for quail eggs. The second phase of the study involved the application of gum based edible coatings for the retention or improvement of the quality of quail eggs. This included the washing of the quail eggs with the selected washing agent and coating of the quail eggs with three post-wash coating solutions (Gum Arabic, Carboxymethylcellulose, and K-Carageenan). Four parameters were monitored, namely, weight loss, pH change, Haugh units, and yolk indices, for a 19 day storage period under room temperature (25-28oC). For all four parameters, there were no significant differences between the control and the treatments; however there were significant differences across the 19-day storage period. The weight loss and pH change were increasing while the Haugh unit and yolk index were decreasing as storage time increases. Since there were no significant differences in the quality parameters of the eggs between the untreated eggs and the treated eggs, as well as among the treatments done to the eggs, it is recommended that any of the edible film coatings be used as a post-wash coating for quail eggs.